Mycobacterium avium subspecies paratuberculosis cultured from locally and commercially pasteurized cow's milk in the Czech Republic - Ayele, Wuhib Y; Svastova, Petra; Roubal, Petr; Bartos, Milan; Pavlik, Ivo (Applied and environmental microbiology, 2005)
Between November 2002 and April 2003, 244 bottles and cartons of commercially pasteurized cow's milk were obtained at random from retail outlets throughout the Czech Republic. During the same period, samples of raw milk and of milk that was subsequently subjected to a minimum of 71.7 degrees C for 15 s in a local pasteurization unit were also obtained from two dairy herds, designated herds A and B, with low and high levels, respectively, of subclinical Mycobacterium avium subsp. paratuberculosis infection, and from one herd, herd C, without infection. Infection in individual cows in each herd was tested by fecal culturing. Milk samples were brought to the Veterinary Research Institute in Brno, Czech Republic, processed, inoculated onto Herrold's egg yolk slants, and incubated for 32 weeks. Colonies were characterized by morphology, Ziehl-Neelsen staining, mycobactin J dependency, and IS900 PCR results. M. avium subsp. paratuberculosis was cultured from 4 of 244 units (1.6%) of commercially pasteurized retail milk. M. avium subsp. paratuberculosis was also cultured from 2 of 100 (2%) cartons of locally pasteurized milk derived from infected herds A and B and from 0 of 100 cartons of milk from uninfected herd C. Raw milk from 1 of 10 (10%) fecal culture-positive cows in herd A and from 13 of 66 (19.7%) fecal culture-positive cows in herd B was culture positive for M. avium subsp. paratuberculosis. These findings confirm that M. avium subsp. paratuberculosis is present in raw milk from subclinically infected dairy cows. The culture of M. avium subsp. paratuberculosis in the Czech Republic from retail milk that had been pasteurized locally or commercially to the required national and European Union standards is in agreement with similar research on milk destined for consumers in the United Kingdom and the United States and shows that humans are being exposed to this chronic enteric pathogen by this route.
Keywords: mléko; Mycobacterium avium subsp. paratuberculosis; DNA, Bacterial; potravinářská mikrobiologie; Česká republika; polymerázová řetězová reakce; Food Microbiology; Polymerase Chain Reaction; vysoká teplota; skot; Czech Republic; paratuberkulóza; Paratuberculosis; DNA bakterií; Base Sequence; sekvence nukleotidů; nemoci skotu; ženské pohlaví; Sterilization; zvířata; Cattle; Hot Temperature; Milk; Cattle Diseases; Female; sterilizace; Animals